Pengaruh Kepemimpinan Kepala Sekolah, Disiplin Kerja dan Komitmen Terhadap Kinerja Guru MAN 5 Bireuen - Latifah, Latifah; Syarifuddin, Evi Arief; A. Rahman, Aisyah (peusangan, 2025)
The study analyzed teacher performance in MAN 5 Bireuen environment by involving the factors of Principal leadership, work discipline and teacher commitment. Using associative research with a quantitative approach and applying path analysis, to prove the developed hypothesis. The results obtained that; (1) there is a causal relationship between the factors of Principal leadership, work discipline and teacher commitment, an average of 0.613. (2) performance is influenced, both directly and indirectly by the principal leadership factor, by 18,59%. Likewise, the teacher discipline factor contributes 39,32% and the commitment of teachers by 20,5%. (3) Simultaneously, Principal leadership, work discipline and teacher commitment have a significant effect on teacher performance with a contribution of 39,8%.